Transcriptome Analysis Reveals Candidate Genes Involved in Gibberellin-Induced Fruit Setting in Triploid Loquat (Eriobotrya japonica) - Jiang, Shuang; Luo, Jun; Xu, Fanjie; Zhang, Xueying (Frontiers in Plant Science, 2016)
The triploid loquat (Eriobotrya japonica) is a new germplasm with a high edible fruit rate. Under natural conditions, the triploid loquat has a low fruit setting ratio (not more than ten fruits in a tree), reflecting fertilization failure. To unravel the molecular mechanism of GA treatment to induce parthenocarpy in triploid loquats, a transcriptome analysis of fruit setting induced by GA3 was analyzed using RNA-seq at four different stages during the development of young fruit. Approximately 344 million high quality reads in seven libraries were de novo assembled, yielding 153,900 unique transcripts with more than 79.9% functionally annotated transcripts. A total of 2,220, 2,974 and 1,614 differentially expressed genes (DEGs) were observed at 3, 7 and 14 days after GA treatment, respectively. The weighted gene co-expression network and Venn diagram analysis of DEGs revealed that sixteen candidate genes may play critical roles in the fruit setting after GA treatment. Five genes were related to auxin, in which one auxin synthesis gene of yucca was upregulated, suggesting that auxin may act as a signal for fruit setting. Furthermore, ABA 8'-hydroxylase was upregulated, while ethylene-forming enzyme was downregulated, suggesting that multiple hormones may be involved in GA signaling. Four transcription factors, NAC7, NAC23, bHLH35 and HD16, were potentially negatively regulated in fruit setting, and two cell division-related genes, arr9 and CYCA3, were upregulated. In addition, the expression of the GA receptor gid1 was downregulated by GA treatment, suggesting that the negative feedback mechanism in GA signaling may be regulated by gid1. Altogether, the results of the present study provide information from a comprehensive gene expression analysis and insight into the molecular mechanism underlying fruit setting under GA treatment in E. japonica.